Neuroendocrine Tumors of the Large Intestine: Clinicopathological Features and Predictive Factors of Lymph Node Metastasis - Kojima, Motohiro; Ikeda, Koji; Saito, Norio; Sakuyama, Naoki; Koushi, Kenichi; Kawano, Shingo; Watanabe, Toshiaki; Sugihara, Kenichi; Ito, Masaaki; Ochiai, Atsushi (Frontiers in Oncology, 2016)
A new histological classification of neuroendocrine tumors (NET) was established in WHO 2010. ENET and NCCN proposed treatment algorithms for colorectal NET. Retrospective study of NET of the large intestine (colorectal and appendiceal NET) was performed among institutions allied with the Japanese Society for Cancer of the Colon and Rectum, and 760 neuroendocrine tumors from 2001 to 2011 were re-assessed using WHO 2010 criteria to elucidate the clinicopathological features of NET in the large intestine. Next, the clinicopathological relationship with lymph node metastasis was analyzed to predict lymph node metastasis in locally resected rectal NET. The primary site was rectum in 718/760 cases (94.5%), colon in 30/760 cases (3.9%), and appendix in 12/760 cases (1.6%). Patients were predominantly men (61.6%) with a mean age of 58.7 years old. Tumor size was less than 10 mm in 65.4% of cases. Proportions of NET G1, G2, G3, and MANEC were 88.4%, 6.3%, 3.9%, and 1.3%, respectively. Of the 760 tumors, 468 were locally resected, and 292 were surgically resected with lymph node dissection. Rectal NET showed a higher proportion of NET G1, and colonic and appendiceal NET was more commonly G3 and MANEC. Of the 292 surgically resected cases, 233 NET G1 and G2 located in the rectum were used for the prediction of lymph node metastasis. Lymphatic and blood vessel invasion were independent predictive factors of lymph node metastasis. NET G2 cases showed more frequent lymph node metastasis than that seen in NET G1 cases, but this was not an independent predictor of lymph node metastasis. Of the 98 surgically resected cases less than 10 mm in size, we found 9 cases with lymph node metastasis (9.2%). All cases were NET G1, and 8 of 9 cases were positive either for lymphatic invasion or blood vessel invasion. Using the WHO classification, we found NET in the large intestine showed a tumor-site–dependent variety of histological and clinicopathological features. Risk of lymph node metastasis in rectal NET was confirmed even in lesions smaller than 10 mm. Concordant assessment of vascular invasion will be required to estimate lymph node metastasis in small lesions.